Si︠e︡vero-zapadnai︠a︡ chastʹ Okhotskago mori︠a︡ po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana sʺ 1910 po 1918 godʺ / Sostavli︠a︡li Shturmana dalʹn. plavinīi︠a︡ I. Ivanovskīĭ, P. Simonʺ i Kapitanʺ mal. plavanīi︠a︡ V. Gragaĭtisʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : [Морское министерство, Главное гидрографическое управленіе], 1918)
Relief shown by form lines and spot heights. Depth shown by soundings and isolines.; Title translation: Northwest part of the Sea of Okhotsk, according to the survey of the Hydrographic Expedition of the Eastern Ocean from 1910 to 1918.; Greenwich meridian Grayscale; 1:150,464